A recurrent intertrigo: benign familial chronic pemphigus - Parajuli, Niraj (Journal of Chitwan Medical College, 2018)
Benign familial chronic pemphigus (BF CP) is an autosomal dominant disorder characterized by recurrent vesicles and plaques mostly over the intertriginous areas. The defect is in the AT P2C1 gene which leads to suprabasilar acantholysis. Pregnancy, physical trauma, excessive sweating, skin infections and exposure to ultraviolet radiation are the important trigger factors. Self-medications or over the counter treatment usually makes a delay in the proper diagnosis.